Universal holonomic quantum gates over geometric spin qubits with polarised microwaves - Kodai Nagata (Nature Portfolio, 2018)
Holonomic quantum gates represent a promising route to noise-tolerant quantum operations. Here, the authors use polarised microwaves to implement nonadiabatic holonomic quantum gates at room temperature and zero magnetic field on NV centers, both on single-qubit and between electron and nuclear spins.